PATRIARCHY, INEQUALITY AND COURTSHIP: DECISION-MAKING INABILITY - Selti; Puji Efriany Zain, Yohanes Yappo, Leonardo Siburian, Lukas (Adisam Publisher, 2023)
This research aims to explore the narratives told to peers about sexual harassment in long-term friendships. This research focuses more on finding narratives that emerge for victims of sexual harassment at the dating level. However, it is still difficult for researchers to find empowerment spaces in which to capture these narratives as data for empowerment spaces in order to see the extent to which narratives are able to resonate in this research as qualitative research or as a research method. The results showed that the research subjects had experienced such a long trauma but were still able to speak out, which often became a space for public silencing when it seemed that sexual harassment was considered a taboo culture